Metodika razrabotki individual'nogo trenirovocnogo plana podgotovki sportsmenov vysokoj kvalifikacii - Mjakincenko, E. B.; Abaljan, A. G.; Lebedev, M. M.; Šestakov, M. P.; Fomicenko, T. G. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The article describes the methodology (algorithm) for writing an individual plan for the training of high-class athletes based on the analysis of athlete`s comprehensive (complex) monitoring data and on the use of standardized forms of planning documentation. The experience of using this method in the Russian national teams for winter sports showed its effectiveness and the possibility of using other kinds of sports as a methodological accompaniment, as well as modern content for refresher courses and retraining of trainers.